2021
DOI: 10.1007/s13201-021-01471-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of water hammer in long water transmission pipeline

Abstract: In the present study, a water transmission pipeline under steady conditions is modeled followed by examining the transient flow created by the failure of pumps in the pipeline. This pipeline is 31 km from the water transmission pipeline of Kerman, Iran. The software analysis results were compared with those of a numerical model for a laboratory test to validate transient flow modeling. While transient flows are created by pump failure, various areas of the water transmission pipelines will be affected by the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The results showed that pipeline diameters had crucial factors that influence hydraulic transient in hydropower plant systems. [16] studied the negative pressure due to the transient flow created by pump failure of the 31 km water transmission pipeline of Kerman City in Iran. It was shown that installing hydropneumatic tanks along the pipeline length in the right places prevented negative pressure.…”
Section: Protection Methods To Resist Water Hammermentioning
confidence: 99%
“…The results showed that pipeline diameters had crucial factors that influence hydraulic transient in hydropower plant systems. [16] studied the negative pressure due to the transient flow created by pump failure of the 31 km water transmission pipeline of Kerman City in Iran. It was shown that installing hydropneumatic tanks along the pipeline length in the right places prevented negative pressure.…”
Section: Protection Methods To Resist Water Hammermentioning
confidence: 99%
“…The fluid mass is equivalent to the wall of the pipeline, only considering its influence on pipeline vibration and ignoring the mutual coupling between the fluid and the pipeline. Assuming the density and volume of the pipeline material are ρ g and V g , and the density and volume of the fluid material are ρ l and V l , the equivalent pipeline density is [26,27]:…”
Section: Vibration Characteristics Analysis Of the Submarine Hydrauli...mentioning
confidence: 99%
“…The water hammer protection measures often used include air vessels, pressure-regulating towers, air valves, water hammer relief valves, and two-stage closing of butterfly valves after pumps, etc. [9][10][11][12]. Among these listed methods, air vessels are used more frequently and with better application results due to their economic and stability advantages [13,14].…”
Section: Introductionmentioning
confidence: 99%